Differences In Selection And Evaluation Criteria Between Arab Versus Western Expatriates Based On Saudi Hr Managers’ Perception - HANSON, ROBERT J. (The journal of contemporary issues in business and government, 2021)
Purpose The main purpose of this study is to evaluate the differences between selection and evaluation criteria among Arab and western expatriates. The employment opportunities are thus the main intention that is found from the perception of the Saudi Arabian HR managers. Methodology Deductive research approach has been chosen for the study and also qualitative as well as hermeneutic phenomenology has been applied for dealing with the perception of the HR managers. The interview process is preferred for gathering the perception and this is done with 21 HR managers of Saudi Arabian companies. The data has been analyzed with thematic coding analysis. Findings-Based on the gathered data from the perception of the HR managers it was found that Western expatriates, they get the better job opportunities from the Arab expatriates as they have more creativity, innovative skills and higher education levels. The management of the Western expatriates is still better than the Arab expatriates. Western expats are getting higher salaries than the Arab expats. However, the small companies select the expats based on their skills and past performances and for the cultural influence, the Arab expats are preferred more. Originality Primary data has been gathered from the HR managers’ interview process. Some statistics has been gathered from the internet sources and journals to analyze the difference between Arab and western expatriates.